Development of Innovative Student Worksheet Using Google Sites for Reproductive System Material - Dani Rahmawati Hakim; Kartika Ratna Pertiwi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine 1) the development of student worksheet based on problem-based learning (PBL) on reproductive system material using Google sites and 2) the feasibility of student worksheet based on problem-based learning (PBL) on reproductive system material for class XI. This research was a research and development using the 4D model, consisted of define, design, develope, and disseminate. Student worksheet was developed using Google Sites. The validity test was carried out with expert judgment by material and media experts. External validity was conducted by biology teachers as practitioners and high school class XI students. The results showed that the results of the development of student worksheet based on Google Sites are in accordance with the 4D development stage and PBL-based student worksheet using Google Sites on reproductive system material are suitable for use based on the material and learning media aspects. Based on the assessment of material experts, learning media experts, and biology teachers as practitioners, this student worksheet is in the "very good" category, while the assessment by students as trial participants is in the "good" category. This student worksheet contains issues related to reproductive health. The media used is based on website mode, so all smartphone users can use it. It can be concluded that PBL-based student worksheet using Google Sites is feasible for use in the implementation of reproductive system biology learning materials